The Effects of Corporate Social Responsibility, Financial Slack, And Environmental Costs on Financial Performance - Wahyuni, Trie Helza; Aira, Aras (Riset Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study aims to analyze the effects of corporate social responsibility, financial slack, and environmental costs on financial performance. The population in this study consists of coal mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2024. Methodology: A quantitative approach was used, and the sample in this study consisted of 13 companies listed on the Indonesia Stock Exchange for the period 2022-2024, which were determined using purposive sampling. Results: The panel data regression analysis results showed that the environmental cost variable affected financial performance, whereas corporate social responsibility and financial slack did not. Conclusions: Financial slack and environmental costs, particularly CSR, play a significant role in improving financial performance in the coal mining sector. Limitations: This study is limited to the coal mining sector, a short observation period (2022–2024), and selected financial ratios, which may not fully cover all the determinants of financial performance. Contribution: This study contributes to the literature by providing empirical evidence on the determinants of financial performance in the coal mining sector, which serves as a useful guide for investors in corporate decision-making.